Motif Lukis Wayang Kamasan Pada Media Keramik - Alit Parwita Yana, I Made; Muka, I Ketut; Rai Sunarini, Ni Made (Hastagina : Jurnal Kriya Seni, 2024)
Abstrak The art of Kamasan wayang painting is the main source of inspiration in the application of ceramic painting in the Kamasan decorative style. The Kamasan Wayang motif is applied to porcelain ceramic media using the on-glaze technique with special ceramic colors which go through a 700°C firing process to permanently bond the color to the porcelain surface in various shapes of concave, convex and flat ceramic media. The main aim of creating the art of Kamasan wayang painting on ceramics is to preserve Bali's rich cultural heritage and show the uniqueness of the phenomenal cultural arts. This practice is rare in the modern ceramics industry, making these works rare on the market. Therefore, it is important to introduce and promote this ceramic painting technique to the wider community. Kamasan wayang paintings on ceramics are not only decorative in a classic style, but are also able to present diverse aesthetics in various media. Decorative ceramics with Kamasan wayang motifs are not only objects of art, but also have potential as functional objects. The process of creating this work of art is carried out carefully at the Roki Ceramik Painting Company, ensuring that each work reflects the quality and authenticity of the work. Through a collaboration between tradition and innovation, the art of Wayang Kamasan painting on ceramics has significant potential to develop and integrate into the global art and design industry. By combining traditional craftsmanship with contemporary innovation, this art can gain a relevant position in the international market